BODIPY Immobilized MCM‐41 Based Multianalyte Sensor: Application in Detection and Removal of Trivalent (Al3+, Cr3+) and Divalent (Cu2+, Hg2+) Metal Ions in Aqueous Media. Issue 7 (28th December 2022) - Chaudhary, Garima; Pratap Singh, Amit
Abstract: In the present study, a novel p ‐phenylcarboxylic acid BODIPY (L ) immobilized MCM‐41 based solid chemosensor material L‐propylsilyl@MCM‐41 (MS4 ) was developed to detect multiple metal ions in a pure aqueous medium. The synthesized solid chemosensor material MS4 shows high sensitivity and removal ability towards trivalent (Al 3+, Cr 3+ ) and divalent (Cu 2+, Hg 2+ ) metal ions. The emission intensity of MS4 enhanced multifold selectively in the presence of trivalent (Al 3+, Cr 3+ ) metal ions and shows quenching in the presence of divalent (Cu 2+, Hg 2+ ) metal ions. The limit of detection was calculated to be in the nanomolar range with Al 3+, Cr 3+, Cu 2+, and Hg 2+ metal ions in the aqueous medium. The spectroscopic and analytical results suggest that MS4 selectively binds with Al 3+ and Cr 3+ through −NH functionality and with Hg 2+ and Cu 2+ through −COOH functionality of p ‐phenylcarboxylic acid BODIPY (L ). Further, MS4 selectively removes Al 3+, Cr 3+, Cu 2+, and Hg 2+ metal ions from the aqueous media with removal efficiency of 97.28 %, 96.34 %, 87.19 %, and 95.63 %, respectively. No noticeable change in the concentration was observed for other metal ions. The recycling potential of MS4 was evaluated using EDTA for up to seven cycles with no significant reduction in sensing capability. Abstract : The p ‐phenylcarboxylic acid BODIPY derivative was synthesized and immobilized on MCM‐41 to produce solid mesoporous sensing material L‐propylsilyl@MCM‐41 (MS4 ). The synthesized material MS4 was used to detect and remove divalent (Cu 2+, Hg 2+ ) and trivalent (Al 3+, Cr 3+ ) metal ions from an aqueous medium. The BODIPY immobilized MS4 shows turn‐ON fluorescence in the presence of Al 3+ and Cr 3+ metal ions and turn‐OFF fluorescence in the presence of Hg 2+ and Cu 2+ metal ions.